INTERNALIZATION OF ISLAMIC EDUCATION VALUES THROUGH THE HABIT OF DHUHA PRAYER AT SMAN 1 SUKRA INDRAMAYU - Saepulah, Saepulah; Parid, Miptah; Raj Chandra, Muhammad; Hadiansyah, Yudi; Al-Sharafi, Mohammed A (Edukasi Islami: Jurnal Pendidikan Islam, 2025)
Background: Student success is often measured by the ability to answer questions, not by the application of the values ​​learned. In fact, instilling religious values ​​is more effective through affective and psychomotor approaches. Therefore, innovative learning is needed that touches the heart and forms real behavior. Purpose: The objectives of this study are to describe and analyze in depth how the internalization of Islamic religious education values occurs through the habit of praying dhuha at SMAN 1 Sukra Indramayu. Method: This research uses a qualitative approach with a case study type , The location of this research is SMAN 1 Sukra Indramayu, data analysis was carried out in three stages, namely data reduction, data presentation, and drawing conclusions. Results: The habit of praying dhuha at SMAN 1 Sukra Indramayu has proven to be an effective strategy in internalizing the values of Islamic religious education through the process of transformation, transaction, and transinternalization of values. This activity not only fosters the habit of worship, but also forms the character of students who are religious, disciplined, and have noble morals, and creates a school culture that is spiritual and harmonious, with active support from educators, parents, and the school environment. Conclusion: The implementation of Dhuha prayer in congregation every Friday serves as a means of forming students' religious character through the integration of cognitive, affective, and psychomotor aspects. Internalization of values ​​is carried out in three stages: transformation of values ​​through theoretical understanding, transaction of values ​​through involvement in worship, and transinternalization when these values ​​become part of students' behavior and self-awareness.